Moisture Transfer Characteristics and Kinetics Determination for Insulated Paperboard in Hot-Pressing Process - Lingbo Kong; Jingyi Zhao; Jiahao Li; Yuejin Yuan (Energies, 2022)
The transport characteristics and kinetics of moisture in hot-pressing are crucial to controlling the insulated paperboard drying process. The effects of operating temperature (110, 120, and 130 °C) on moisture transfer characteristics of an insulated paperboard were investigated. The results showed that the hot-pressing process consists of four successive stages, i.e., the warm-up stage, the boiling-point temperature stabilization stage, the temperature slowly rising stage, and the constant temperature stage. It was observed that a higher temperature mainly affected the medium and later stages of the hot-pressing process. When the operating temperature increased from 110 to 130 °C, the maximum value of the drying rate increased by 16.04%, and the drying time decreased by 62.50% consequently. Furthermore, a new mathematical model used to describe the moisture transfer kinetics for the insulated paperboard hot-pressing was developed in this paper. The results from the proposed new model were evaluated with another eight commonly used models. It showed better predictions and satisfactorily described the moisture transfer kinetics of the insulated paperboard compared with other models under the investigated hot-pressing conditions. The values of R2, χ2, and root mean square error (RMSE) of the new model varied from 0.99961 to 0.99999, 0.00001 to 0.00005, and 0.00120 to 0.00599, respectively.